The Relationship Between Obesity and Smoking to Hypertension Incidence - Tifani Lasianjayani; Santi Martini (Universitas Airlangga, 2014)
Hypertension is a disease that causes morbidity and mortality in 20-50% of total deaths. Obesity and smoking are risk factors for hypertension. This study aims to determine the relationship between obesity, and smoking on the incidence of hypertension. The study was conducted with a cross-sectional design involving 75 people and was taken using simple randomization techniques from patients seeking treatment at the cardiology clinic in Public Hospital of Haji Surabaya in May 2014. The variables studied were gender, obesity, and smoking behavior. Smoking behavior that was studied consisted of smoking history, use of filters, duration of smoking, number of cigarettes, and types of cigarettes. Data were analyzed using Chi-Square test. The incidence of hypertension found in this study was 45 people (60%). 64.4% of people with hypertension are women. The analysis showed a significant relationship between obesity and the incidence of hypertension (p = 0.014) with a strong relationship of 0.299. History of smoking (p = 0.211), use of filters (p = 0.378), duration of smoking (p = 1,000), smoking criteria (p = 0.848) and types of cigarettes (p = 0.673) showed no significant relationship. The conclusion of this study is obesity is related to the incidence of hypertension.